2020
DOI: 10.1371/journal.pone.0228966
|View full text |Cite
|
Sign up to set email alerts
|

The inability to walk unassisted at hospital admission as a valuable triage tool to predict hospital mortality in Rwandese patients with suspected infection

Abstract: Objective To assess the value of the inability to walk unassisted to predict hospital mortality in patients with suspected infection in a resource-limited setting. Methods This is a post hoc study of a prospective trial performed in rural Rwanda. Patients hospitalized because of a suspected acute infection and who were able to walk unassisted before this disease episode were included. At hospital presentation, the walking status was graded into: 1) can walk unassisted, 2) can walk assisted only, 3) cannot walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As evidenced by the Rwandan trial, inability to walk unassisted at hospital presentation had a low specificity (20%) but was 100% sensitive (CI 95%, 90-100%) to predict in-hospital death, recommending that it could be used as simple and reliable triage tool with a high sensitivity to predict in-hospital mortality. 19 Patients with low WBC counts (leukopenia) at admission to hospital had three times higher in-hospital mortality than those with normal WBC counts (AHR=3.16, 95% CI; (1.55, 6.41). This finding was supported by the Japan study (OR: 0.28, 95% CI: 0.11-0.73) In addition, Uganda research found a high prevalence of low WBC count (leukopenia) with low CD4+ lymphocytes in TB patients with no HIV co-infection during inpatient treatment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As evidenced by the Rwandan trial, inability to walk unassisted at hospital presentation had a low specificity (20%) but was 100% sensitive (CI 95%, 90-100%) to predict in-hospital death, recommending that it could be used as simple and reliable triage tool with a high sensitivity to predict in-hospital mortality. 19 Patients with low WBC counts (leukopenia) at admission to hospital had three times higher in-hospital mortality than those with normal WBC counts (AHR=3.16, 95% CI; (1.55, 6.41). This finding was supported by the Japan study (OR: 0.28, 95% CI: 0.11-0.73) In addition, Uganda research found a high prevalence of low WBC count (leukopenia) with low CD4+ lymphocytes in TB patients with no HIV co-infection during inpatient treatment.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, a study from Brazil reported a mortality rate of 31.8%, which was complementary to our study, and a higher mortality rate of 37.5% was observed from study from the Philippines, as both the Philippines, Brazil, as well as Ethiopia are among the 30 high TB burden countries. 1,19,20 The cumulative probability of death was 3.31% (95% CI: 2.60, 4.14), 4.32% (95% CI: 3.28, 5.52) and 7.57% (95% CI: 5.71, 9.06) at the end of 28, 56, and 84 days of observation respectively, which suggests that the risk of death increases with the number of days the patient stayed in the hospital. More than half (56%) (n=34) of the deaths occurred during the first week of admission.…”
Section: Discussionmentioning
confidence: 99%
“…This appears physiologically sound and might not only reflect the degree of frailty [ 15 ] but also the extent to which the patient’s physiologic reserve has been compromised by the acute condition. Similarly, the inability to walk at hospital admission proved to be an accurate predictor of the risk of in-hospital death in three African studies [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, clinicians should diagnosis sepsis in the context of a patient with infection and any available clinical or biochemical marker of end organ dysfunction. This should include features such as reduced consciousness and inability to stand and walk independently which has been shown to be associated with higher mortality in Africa [ 17 , 21 ].…”
Section: Essaymentioning
confidence: 99%